Sosialisasi Dan Implementasi Pemeriksaan Kadar Hba1c Pada Pasien Diabetes Mellitus Di Wilayah Kerja Puskesmas Bogor - Wijayanti, Lumastari Ajeng; Harfika, Meiana; Wijayanti, Azmi; Halmar, Halbina Famung; Zulaika, Zulaika; Amelia, Inneke Mutiara; Utami, Dia Rejeki (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
People with diabetes mellitus need blood glucose examination to control blood glucose levels and prevent hyperglycemia, one of the examinations that is useful for controlling diabetes mellitus is HbA1C. Objective: To provide knowledge about HbA1c level examination to patients with type 2 diabetes mellitus. Method Socialization and implementation activities of hba1c level examination in patients with diabetes mellitus in the Bogor Health Center Working Area followed by patients with type 2 diabetes mellitus. A pre-test was given before the counseling continued with HbA1c level examination and provision of material on preventing diabetes mellitus using poster and leaflet media. The results showed that there was a difference in the pre-test and post-test results of the counseling participants with an average post-test value higher than the average pre-test value of the participants. The conclusion is that there is an increase in knowledge about preventing diabetes mellitus in patients with type 2 diabetes mellitus in the Bogor Health Center Working Area.